Behavioral aging is associated with reduced sensory neuron excitability in Aplysia californica - Kempsell, Andrew T.; Fieber, Lynne A. (Frontiers in Aging Neuroscience, 2014)
Invertebrate models have advantages for understanding the basis of behavioral aging due to their simple nervous systems and short lifespans. The potential usefulness of Aplysia californica in aging research is apparent from its long history of neurobiological research, but it has been underexploited in this model use. Aging of simple reflexes at both single sensory neuron and neural circuit levels was studied to connect behavioral aging to neurophysiological aging. The tail withdrawal reflex (TWR), righting reflex, and biting response were measured throughout sexual maturity in three cohorts of hatchery-reared animals of known age. Reflex times increased and reflex amplitudes decreased significantly during aging. Aging in sensory neurons of animals with deficits in measures of the TWR and biting response resulted in significantly reduced excitability in old animals compared to their younger siblings. The threshold for firing increased while the number of action potentials in response to depolarizing current injection decreased during aging in sensory neurons, but not in tail motoneurons. Glutamate receptor-activated responses in sensory neurons also decreased with aging. In old tail motoneurons, the amplitude of evoked EPSPs following tail shock decreased, presumably due to reduced sensory neuron excitability during aging. The results were used to develop stages of aging relevant to both hatchery-reared and wild-caught Aplysia. Aplysia is a viable aging model in which the contributions of differential aging of components of neural circuits may be assessed.